Challenges in Conserving Soapstones in the National Museum, Esie, Nigeria - Oyinloye, Micheal Abiodun (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Esie Museum in Kwara State is the oldest national museum in Nigeria and it is reputed to have the largest collection of soapstone images across Africa. The soapstone images and other materials in the museum stand out as a unique art tradition of Nigeria that must be preserved against deterioration or total breakdown so that ancient civilization would not be forgotten. In order to preserve these cultural objects, proper caring methods and techniques must be followed to guarantee the long lifespan of the collections. It is against this background that the study examines the essence of conservation of the soapstone images in the National Museum, Esie. It also examines National Museum, Esie's collections and the challenges of conservation. Data for this study were collected from both primary and secondary sources. The primary source draws from fieldwork which includes physical observation of the objects in the museum, oral interviews with the purposeful key informants, such as the curators and the conservators in the museum, as well as the traditional ruler of Esie community. The secondary sources were collected from existing literature, such as textbooks, journal articles and protagonists in the subject matter. Findings of the study reveal inadequate care and maintenance of the cultural heritage in this museum. Subsequently, the study suggests a need to improve the facilities and equipments at the museum, so as to guarantee the well-being of objects kept in the museum.